Highly efficient perovskite solar cells based on mechanically durable molybdenum cathode - Jeong, Inyoung; Kim, Hae Jin; Lee, Byung-Seok; Son, Hae Jung; Kim, Jin Young; Lee, Doh-Kwon; Kim, Dae-Eun; Lee, Jinwoo; Ko, Min Jae (ELSEVIER SCIENCE BV, 2015)
Noble metal-free mesoscopic perovskite solar cell based on low-cost molybdenum (Mo) cathode has been developed for the first time. By optimizing the thickness of Mo electrode and combination with high quality perovskite layer, the Mo cathode-based perovskite solar cell exhibited a best power conversion efficiency as high as 15.06% with invariance of current density-voltage curves at different scan rates and very small hysteresis according to scan direction. In addition to photovoltaic performances, importance of mechanical durability of a cathode material for perovskite solar cell was highlighted and results from nano-indentation and scratch test indicated that Mo electrode has superior resistance and restoration capability against external scratch or deformation compared to Au electrode. The Mo cathode-based perovskite solar cells have great potential for realizing low cost and high performance as well as mechanical durability. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: HOLE-CONDUCTOR-FREE; HALIDE PEROVSKITES; PERFORMANCE; ELECTRON; LIGHT; INTERFACE; HARDNESS; LENGTHS